2015
DOI: 10.1177/1049731515598619
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for School Refusal Among Children and Adolescents

Abstract: Objective: School refusal is a psychosocial problem associated with adverse short-and long-term consequences for children and adolescents. The authors conducted a systematic review and meta-analysis to examine the effects of psychosocial treatments for children and adolescents with school refusal. Method: A comprehensive search process was used to find eligible randomized controlled trials and quasi-experimental studies assessing the effects of psychosocial treatments on anxiety or attendance outcomes. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 52 publications
2
95
1
14
Order By: Relevance
“…Maynard, Heyne et al. () describe the contents of five CBT manuals for treating school refusal (Heyne & Rollings, ; Heyne, Sauter, & Van Hout, ; Kearney & Albano, ; Last, ; Tolin et al., ). All but one (Last, ) utilise a form of individualised treatment based upon the functions served by the nonattendance together with consideration of ‘predisposing, precipitating, perpetuating, and protective factors’ (Maynard, Heyne et al., p. 3).…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Maynard, Heyne et al. () describe the contents of five CBT manuals for treating school refusal (Heyne & Rollings, ; Heyne, Sauter, & Van Hout, ; Kearney & Albano, ; Last, ; Tolin et al., ). All but one (Last, ) utilise a form of individualised treatment based upon the functions served by the nonattendance together with consideration of ‘predisposing, precipitating, perpetuating, and protective factors’ (Maynard, Heyne et al., p. 3).…”
Section: Treatmentmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis (Maynard, Brendel et al., ; Maynard, Heyne et al. ()) identified six RCTs involving psychosocial interventions for school refusal (with five studies utilising CBT). Two further studies reviewed incorporated a quasi‐experimental design.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority continues to have significant impairment needing professional help. The results of a recent systematic review provide support for cognitive behaviour therapy (CBT) for the treatment of children and adolescents with school refusal, at least for the improvement of school attendance . Very few studies have used a rigorous methodology in assessing the efficacy of treatments.…”
Section: Managementmentioning
confidence: 99%
“…Previous studies have shown that somatic complaints associated with emotional distress are common features of school refusers (Honjo, Kasahara, & Ohtaka, 1992), and in some cases, headaches, stomach aches, nausea, fever, and vomiting have been reported (Blagg, 1987;Heyne & King, 2004). General clinical interventions for school refusal have mainly focused on CBT, which has provided clear evidence regarding its overall effectiveness (Bernstein, Hektner, Borchardt, & McMillan, 2001;Heyne et al, 2002;Maynard et al, 2015;Last, Hansen, & Franco, 1998;Ollendick & King, 1999;Wimmer, 2008). CBT for school refusal generally employs psychoeducation, cognitive restructuring, contingency contracting, parental-management strategies, and exposure, all of which are based on a detailed assessment and functional analysis of the child and his/her parents (King & Bernstein, 2001).…”
Section: Application Of Morita Therapy For School Refusalmentioning
confidence: 99%